Religious Education and The Emergenc Of Schools in The Christian Middle Ages - حميدوش لينا (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research discussed the nature of religious education in the Christian Middle Ages , so it delt with the first problems that stemmed from it , and were related to the dissemination of education and taking it out monasteries and churches to public schools . The research also discussed the development of the concept of religious education for schools, up to the Scholastic stage including its philosophical and theological issues. It discussed as well the effect of other cultures on this religious schools , like Greek and Arabic Islamic culture, and how they affected the nature of education and its problems .